Policy on the Provision of Contraceptive Devices for School-Aged Children and Adolescents from the Perspective of Legal Utility - Asfa Asfiais Sholihah (Universitas Airlangga, 2025)
The policy on providing contraceptive devices for school-aged children and adolescents in Government Regulation No. 28 of 2024 on Health does not clarify the qualifications of children and adolescents eligible to receive contraceptive provisions, allowing room for negative interpretations. This study aims to analyze the underlying considerations of the policy while assessing whether the provision of contraceptive devices for school-aged children and adolescents aligns with the principle of utility as a legal objective. This research employs a normative legal method using statutory, conceptual, and comparative approaches. The findings indicate that Indonesia is still striving to reduce the high maternal and infant mortality rates. Given the still-high prevalence of child marriage, this policy is intended to lower maternal and infant mortality rates caused by high-risk pregnancies among adolescent couples engaged in early marriage. In terms of fulfilling fundamental human rights and the significant positive impact of the policy, it essentially reflects the aspect of legal utility.